Дзета-потенціал як ключовий параметр електрокінетичної взаємодії в біофізичних, мікрофлюїдних та нафтогазових системах⁷ - Фик, Михайло Ілліч; Білецький, Володимир Стефанович (Національний технічний університет "Харківський політехнічний інститут", 2026)
У роботі запропоновано узгоджений електродинамічно-гідродинамічний підхід до моделювання електрокінетичних процесів у дисперсних, біологічних та пористих середовищах на основі явного врахування дзета-потенціалу (ζ) як визначального параметра міжфазної електростатичної взаємодії. Показано, що ζ повинен розглядатися не як допоміжна експериментальна характеристика, а як гранична умова, яка з’єднує рівняння Пуассона–Больцмана та Нав’є–Стокса через електрокінетичний член. Розроблено узгоджену систему рівнянь, у якій ζ вводиться як потенціал на площині гідродинамічного ковзання, що дозволяє коректно описувати приповерхневі швидкості, довжину ковзання, гідрофобно-гідрофільну поведінку та електрокінетичний коефіцієнт зв’язку в пористих середовищах. Проведено чисельну та статистичну валідацію моделі, яка демонструє лінійну залежність швидкостей ковзання від ζ (R² > 0,98) та квадратичний вплив ζ на потенціал міжчастинкового відштовхування в межах DLVO-підходу. Показано, що похибка у визначенні ζ на рівні ±10 % призводить до зміни електроосмотичної швидкості на ±10 %, а електростатичної складової потенціалу взаємодії — до ±21 %, що підтверджує критичну роль точності його визначення. Отримані результати підтверджують, що більш точне врахування ζ є логічним розвитком класичної електрокінетики і дозволяє розширити застосовність системи Максвелла–Нав'є–Стокса для опису систем із вираженою міжфазною поляризацією.

This study proposes a consistent electrohydrodynamic framework for modeling electrokinetic processes in dispersed, biological, microfluidic, and porous media based on the explicit incorporation of the zeta potential (ζ) as a governing parameter of interfacial electrostatic interaction. Research Objective. The primary objective of the research is to develop and validate a physically consistent mathematical model in which the zeta potential is treated not as an auxiliary experimental characteristic, but as a fundamental boundary condition linking electrostatic and hydrodynamic subsystems in electrokinetic phenomena. Scientific Problems. Addressed The study resolves the following scientific problems: 1. Formulation of a coupled Poisson–Boltzmann–Navier–Stokes system with ζ explicitly introduced at the hydrodynamic slip plane. 2. Elimination of inconsistencies arising from substituting surface potential for electrokinetic potential in boundary conditions. 3. Quantitative evaluation of the sensitivity of electroosmotic velocity and interparticle interaction energy to variations in ζ. 4. Statistical validation of the linear and quadratic dependencies predicted by electrokinetic theory. It is demonstrated that ζ must be interpreted as a boundary parameter connecting the Poisson Boltzmann equation and the Navier–Stokes equations through the electrokinetic coupling term. A consistent system of equations is developed in which ζ is introduced as the electric potential at the hydrodynamic shear plane. This formulation enables physically accurate description of near-surface velocity fields, slip length, hydrophobic–hydrophilic behavior, and the electrokinetic coupling coefficient in porous media. Numerical and Statistical Validation. Numerical simulations and statistical analysis confirm:  A linear dependence of slip velocity on ζ (R² > 0.98), consistent with Smoluchowski theory.  A quadratic dependence of electrostatic repulsion energy on ζ within the DLVO framework. Sensitivity analysis shows that a ±10% uncertainty in ζ results in:  ±10% variation in electroosmotic velocity,  approximately ±21% variation in the electrostatic component of interparticle interaction energy. These results quantitatively confirm the critical role of accurate determination in predictive electrokinetic modeling. Scientific Novelty The main scientific novelty lies in:  Treating ζ as an explicit boundary condition within the coupled Maxwell–Navier–Stokes framework;  Providing a mathematically consistent formulation that separates surface potential from electrokinetic potential;  Demonstrating, through validated numerical analysis, the sensitivity hierarchy of electrohydrodynamic parameters to ζ;  Extending the applicability of classical electrokinetics without introducing speculative or non-validated physical assumptions. Practical Significance. The proposed framework improves predictive reliability in:  Microfluidic device optimization,  Biophysical modeling of intercellular electrostatic interactions,  Stability analysis of colloidal and bio-colloidal systems,  Electrokinetic transport in porous geological formations relevant to oil and gas recovery,  Evaluation of hydrophobicity–hydrophilicity and slip behavior in interfacial systems. The findings demonstrate that more accurate consideration of ζ represents a logical advancement of classical electrokinetics and expands the applicability of the Maxwell–Navier Stokes system for systems characterized by pronounced interfacial polarization effects.
Zeta potential as a key parameter of electrocinetic interaction in biophysical, microfluid and oil and gas systems
Keywords: дзета-потенціал; біофізичні системи; мікрофлюїдні технології; нафтогазові системи; подвійний електричний шар; ПЕШ; zeta potential; biophysical systems; microfluidic technologies; oil and gas systems; Double layer; surface science